The HSP90 inhibitor RGRN‐305 exhibits strong immunomodulatory effects in human keratinocytes. Issue 6 (3rd March 2021) - Hansen, Rikke S; Thuesen, Katrine K. H.; Bregnhøj, Anne; Moldovan, Liviu I.; Kristensen, Lasse S.; Grek, Christina L.; Ghatnekar, Gautam S.; Iversen, Lars; Johansen, Claus
Abstract: Keratinocytes are the key cellular target for IL‐17A‐mediated effects in psoriasis and HSP90 is important for IL‐17A‐mediated signalling. RGRN‐305 is a novel HSP90 inhibitor reported to reduce psoriatic phenotypes in preclinical animal models. The aim of this study was to investigate the effect of RGRN‐305 on a psoriasis‐like inflammatory response in human keratinocytes in vitro. Using RT‐qPCR, we demonstrated a significantly increased expression of the HSP90 isoforms HSP90AB1, HSP90B1 and TRAP1 in lesional compared with non‐lesional psoriatic skin. In a psoriasis‐like setting where keratinocytes were stimulated with TNFα and/or IL‐17A, we analysed the mRNA expression using the NanoString nCounter technology and demonstrated that the HSP90 inhibitor RGRN‐305 significantly reduced the IL‐17A‐ and TNFα‐induced gene expression of a number of proinflammatory genes, including the psoriasis‐associated genes CCL20, NFKBIZ, IL36G and IL23A . In agreement with the mRNA data, the protein level of CCL20, IκBζ and IL‐36γ were inhibited by RGRN‐305 as demonstrated by western blotting and ELISA. Interestingly, when keratinocytes were stimulated with a TLR3 agonist, RGRN‐305 also demonstrated potent immunomodulatory effects, significantly inhibiting poly(I:C)‐induced expression of the proinflammatory genes TNFα, IL1B, IL6 and IL23A . Taken together, our data support a role for HSP90 not only in the pathogenesis of psoriasis, but also in broader immune responses. Therefore, HSP90 provides an attractive target for the treatment of psoriasis and other diseases where the innate immune system plays an important role.